Inquiry based learning in software engineering education: exploring students’ multiple inquiry levels in a programming course - Ahmed, Sohaib; Bukhari, Syed Ahmed Hassan; Ahmad, Adnan; Rehman, Osama; Ahmad, Faizan; Ahsan, Kamran; Liew, Tze Wei (Frontiers in Education, 2025)
Learning programming is becoming crucial nowadays for producing students with computational thinking and problem-solving skills in software engineering education. In recent years, educators and researchers are keen to use inquiry-based learning (IBL) as a pedagogical instructional approach for developing students’ programming learning skills. IBL instructions can be provided to students through four inquiry levels: confirmation, structured, guided, and open. In the literature, most of the IBL applications follow only one form of inquiry level to explore observed phenomena. Therefore, the purpose of this paper is to explore multiple inquiry levels in a programming course taught in a software engineering program. For this purpose, MILOS (Multiple Inquiry Levels Ontology-driven System) was developed using activity-oriented design method (AODM) tools. AODM is an investigative framework to identify the significant elements of the underlying human activity. In MILOS, students were involved in different inquiry levels to answer the questions given related to the programming concepts taught in their classes. Further, MILOS was evaluated with 54 first-year software engineering students through an experiment. For the comparison, Sololearn, an online programming application, was tested with 55 first-year software engineering students. Both these applications were evaluated through Micro and Meso levels of the M3 evaluation framework. The Micro-level investigates usability aspects of MILOS and Sololearn while the Meso level explores the learners’ performances using these applications. Overall, the results were promising as students outperformed using MILOS as compared to Sololearn application.